Adaptive fuzzy PI output feedback bounded control for a class of switched nonlinear systems with input constraint. Issue 16 (9th December 2020) - Li, Hongyao; Sun, Haibin; Hou, Linlin
Abstract : In this paper, the problem of adaptive fuzzy proportional integral (PI) output feedback control is addressed for nonstrict-feedback switched nonlinear systems. An adaptive output feedback control scheme is developed, in which the virtual control laws and the final controller are bounded. The bounds are known in advance, and they can be ascertained using the feedback control gains. The first step is to construct a state observer that can estimate the unmeasurable states. The second step is to design an adaptive fuzzy PI output feedback bounded controller by using backstepping method and fuzzy logic systems technique. To guarantee the virtual control laws and a final controller with a specific range, hyperbolic tangent functions and projection operator are introduced. Subsequently, the boundedness of all signals of the closed-loop system is proven via the average dwell time method and Lyapunov stability theory. Simulation results are employed to verify the effectiveness of the developed scheme.